Improving butenyl-spinosyn production in Saccharopolyspora pogona through combination of metabolic engineering and medium optimization - Zhao, Xueli; Lu, Haisong; Peng, Sen; Hang, Haifeng; Aldahmash, Waleed; Al-Ghadi, Muath Q.; Tang, Weihua; Pei, Jiang; Xun, Wan; Guo, Meijin; Mohsin, Ali (Frontiers in Microbiology, 2025)
Butenyl-spinosyn is a high-quality biological insecticide produced by Saccharopolyspora pogona that effectively targets a broad range of insect pests. However, the large-scale production of this insecticide is hindered by its low yield. Herein, based on prior comparative genomic analysis, five mutations were individually overexpressed in aG6. Subsequently, the combinatorial overexpression of sp1322 (encoding NAD-glutamate dehydrogenase) and sp6746 (encoding dTDP-glucose 4,6-dehydratase) in aG6 resulted in strain O1322-6746. The production of butenyl-spinosyn in O1322-6746 was 77.1% higher than that in aG6. Comparative targeted metabolomic analysis uncovered that O1322-6746 exhibited increased metabolic flux toward butenyl-spinosyn precursors. Furthermore, single-factor experiments, Plackett-Burman analysis and response surface methodology were performed to optimize the fermentation medium for O1322-6746. Ultimately, butenyl-spinosyn production was enhanced to 298.5 mg/L in a 5-L bioreactor, marking the highest yield ever reported. This work demonstrated that combining metabolic engineering with medium optimization is an effective strategy to improve butenyl-spinosyn production.